The Implementation of the Sociopreneur Strategy in the Role of Raharjo Village Owned Enterprises (BUMDES) in the Development of the Strawberry Barn Tourist Village, Batu City - Desembrianita, Eva; Maruf, Nirwanto; Wijayanti, Tri Cicik; Wasik, Zainul; Jumadi, Jumadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study is to investigate the sociopreneur-based business strategies are implemented by the manager of Raharjo BUMDes in developing a tourist village in the "Strawberry Granary” plantation area, Pandanrejo District, Batu City. As a leading sector, BUMDes consider the resources they have by using sociopreneur strategies and models as alternative solutions in managing tourism businesses. This type of research was descriptive qualitative. The research informants consisted of 6 people, namely the Head of Raharjo BUMDes and administrators, executor of tourism business operations, and BUMDes partners. The results showed that BUMDes had used a sociopreneur-based tourist village management strategy through tourism businesses.  Several strategic steps and innovations had been carried out: 1. Building a network among stakeholders; 2. Building a Tourist Village Icon; 3. Stabilizing the Strawberry trading system; 4. Expanding market access; 5. Marketing through social media; 6. Expansion of tourism service products; 7. Sociopreneur Implementation. In conclusion, the strategy carries out is able to optimize the available resources into a social capital that could be synergized as a solution in developing the Strawberry Barn tourist village.